EFFECT OF BREEDING AND NON BREEDING SEASONS ON POST THAW QUALITY OF STALLION SEMEN - KUMAR, DEVENDER; JHAMB, DINESH; KUMAR, NAVEEN; SAXENA, ATUL (The Indian Journal of Animal Reproduction, 2023)
Present study was aimed to compare the different cryoprotective agents for semen of Indian stallions during the breeding season (BS) and non breeding season (NBS). Basic extender used was INRA 82 added with 2 per cent egg yolk. The freezing extenders contained the basic extender added with any of the three different cryoprotectants viz dimethyl formamide (DMF), glycerol (GLY) and ethylene glycol (EG) added singly or in combination. The freezing extender E1 contained 2% DMF, E2 contained 2% GLY, E3 contained 2% EG and extender E4 contained 1 % DMF + 1 % GL Y. Semen was thawed at 60°C for 8 sec and post thaw per cent motility (M), viability (V) and positive sperms to HOST (H) was assessed. The minimum M was found in E1 (26.51 ± 01.20 %) and E2 (36.38 ± 2.07 %) in BS and NBS respectively, while maximum M was found in E4 (28.74 ± 1.39 %) and E1 (39.12 ± 02.08 %). The minimum V was found in E1 (22.63 ± 01.19 %) and E3 (29.72 ± 01.52 %) in BS and NBS respectively, while maximum was observed in E4 (26.52 ±1.23%), and E2 (32.83 ± 01.67 %). Minimum H was found in E2 (28.60 ± 01.36 %) and (46.00 ± 02.11 % ) in BS and NBS respectively, however, maximum H was found in semen cryopreserved in E4 (32.63 ± 01.01 %) and (49.03 ± 01.96 %). Overall extender E4 proved best for cryopreserving stallion semen in Indian conditions followed by E1. While comparing the seasons, the overall values for M, V & H were significantly higher in NBS as compared to BS.